The effects of dapagliflozin on kidney and cardiovascular outcomes in patients with chronic kidney disease with and without heart failure. (14th October 2021) - Heerspink, J L; Wheeler, D C; Vart, P; Jongs, N; Hou, F F; Langkilde, A M; Correa-Rotter, R; Rossing, P; Sjostrom, C D; Toto, R D; Chertow, G M; Stefansson, B V; et al.
Abstract: Background: Heart failure (HF) is highly prevalent in patients with chronic kidney disease (CKD) and the severity of kidney impairment increases risk of HF, highlighting the deleterious interplay between the conditions. The DAPA-CKD trial showed that dapagliflozin reduced the risk of kidney failure and HF hospitalization in patients with CKD. Purpose: This prespecified analysis of DAPA-CKD aimed to determine the effects of dapagliflozin on kidney, cardiovascular and mortality outcomes according to presence or absence of HF. Methods: DAPA-CKD (NCT03036150) was a randomized, double blind, controlled trial, which enrolled 4, 304 participants with CKD. Participants were randomized to dapagliflozin 10 mg/day or placebo, as adjunct to standard care, and were followed for a median 2.4 years. The primary endpoint was a composite of sustained decline in eGFR ≥50%, end-stage kidney disease, or renal or cardiovascular death. Key secondary endpoints included a composite of cardiovascular death or HF hospitalization and all-cause mortality. Results: Overall, 468 (11%) participants had a HF diagnosis at baseline. Participants with HF were older (65.3 vs 61.4 years) and more frequently diagnosed with type 2 diabetes (77% vs 66%) compared with those without HF; mean eGFR was similar (43.2 vs 43.1 mL/min/1.73m 2 ) in the two groups. The primary outcome occurred more frequently in those with versus without HF (8.8 vs 5.7 events per 100 patient-years, respectively). The effect of dapagliflozin on the primary outcome was consistent among those with (hazard ratio [HR] 0.58; 95% CI 0.37, 0.91) or without HF (HR 0.62; 95% CI 0.51, 0.75; p-interaction 0.59). The composite of cardiovascular death or HF hospitalization (HR 0.68; 95% CI 0.44, 1.05 vs 0.70; 95% CI 0.51, 0.97; p-interaction 0.90), and the relative risk reduction for mortality (HR 0.56; 95% CI 0.34, 0.93; vs 0.73; 95% CI 0.54, 0.97; p-interaction 0.39) were also consistent in those with or without HF. Conclusion: Patients with co-existing CKD and HF are at high risk of kidney and cardiovascular events and premature mortality. Dapagliflozin consistently reduced the proportional risk of these events, regardless of the presence or absence of HF. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZeneca